THE EFFECT OF GOVERNMENT ACCOUNTING STANDARDS BASED ON AKRUAL, USING INFORMATION TECHNOLOGY, INTERNAL GOVERNMENT CONTROL SYSTEM AND ORGANIZATION COMMITMENT TO QUALITY OF CENTRAL GOVERNMENT FINANCIAL REPORT - Januarti Tiurmaida (Universitas Pamulang, 2018)
The purpose of this study is to determine the effect of the implementation of Accounting Standards Based on Accrual Government, Utilization of Information Technology, Government Internal Control System, and Organizational Commitment to the quality of Central Government Financial Report. Central Government Financial Report is an accountability report on budget execution by Ministry / Institution. The population of research is conducted on the Ministry / Institution, with data acquisition by distributing questionnaires to the compilers of financial statements. The use of method in this research is quantitative with causal relation which is research to know influence between one independent variable (Accrual Based Government Accounting Standards, Information Technology, Government Internal Control System and Organizational Commitment) to dependent variable (Quality of Central Government Financial Report). The results of the study prove that all independent variables positively affect the quality of the Central Government Financial Statements.